Lepironia Articulata as a Sustainable Acoustic Absorber - Ahmad Shafii, Nur Hidayah; Zainulabidin, Muhd Hafeez (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Lepironia articulata is found abundant in a swamp and along streams in West Malaysia and it is commonly used for grey water treatment, numerous traditional craft and now commercialise as an organic straw. However, there is a scarcity of knowledge on the physical and acoustical properties of this natural fibre. Therefore, this study was to determine the potential of Lepironia articulata as an acoustic absorber. The absorption coefficient was tested using the impedance tube method (ASTM E1050-98) for four different structure arrangements, namely “axial”, “horizontal”, “crossed” and “combination” made up of Lepironia articulata with the diameter ranging from 2 to 4 mm and 4 to 7 mm respectively and the thickness remains at 50 mm. The influence of air gap of 0 to 25 mm, in 5 mm increment was introduced in each sample and other physical properties such as density, porosity and tortuosity were investigated. The results revealed that the Lepironia articulata in horizontal, crossed and combination arrangements showed the greatest absorption performance especially in the low-frequency range compared to the axial arrangement. If compared between samples with the range diameter of 4 to 7 mm and 2 to 4 mm, bigger stalks diameter in axial arrangement exhibits the least NRC value. Next, air gaps have a great influence at the low-frequency range whereby it shifted the peaks and sound absorption coefficient curve toward lower frequency. Sound absorption coefficient increases as porosity increase and decrease as density-tortuosity increase. Overall, Lepironia articulata has the potential to be used as a sustainable acoustic absorber as all the samples has NRC value more than or equal to 0.20.